Involvement of ryanodine receptor in skeletal muscle fatigue - Watanabe, D. (Japanese Journal of Physical Fitness and Sports Medicine, 2018)
Ryanodine receptors (RyRs) are tetrameric Ca2+ release channels of sarcoplasmic reticulum (SR). This review attempts to detail the key mechanism of RyR channel gating and to discuss the hypothesis that skeletal muscle fatigue, defined as reduced force production, would result from functional changes in both individual RyR channel opening and coupling among RyR channels. Previous studies have shown that RyR channels in skeletal muscle open simultaneously, called coupled gating, because of physical interaction among channels. In this review, mechanisms underlying muscle fatigue are discussed with consideration of the coupling effect. Fatigue mechanisms are thought to be different between acute exercise and long-term exercise training. The impairments in individual channel opening and coupling between RyR channels can occur after acute exercise, leading to decreased SR Ca2+ release and force depression. On the contrary, during long-term exercise training, individual channel opening would be enhanced but coupling between channels would be impaired. If this were to continue for long periods, SR Ca2+ content would reduce, leading to less Ca2+ release and lower force production.